Incorporação de modelos termodinâmicos na modelagem matemática de processos de extração supercrítica - Silva, Rodrigo Scopel (2013)
Clove (Syzygium aromaticum) essential oil is widely cultivated on eastern countries and has antifungal, antibacterial, insecticidal, and antioxidant properties. Given its vegetal structure, Clove essential oil can be extracted by supercritical fluid. The aim of this work is to model the solubility and the mass transfer process of clove essential oil in supercritical carbon dioxide. For the thermodynamic modeling, the Peng Robinson equation of state was coupled with four mixing rules: van der Waals 1 (vdW1), van der Waals 2 (vdW2), Mathias-Klotz-Prausnitz (MKP) and LCVM. Isothermal vapor-liquid equilibria calculation of CO2/clove essential oil were conducted as a binary system and CO2/eugenol/β-caryophyllene as a ternary system, where the oil composition is defined from major oil compounds, i.e., eugenol and β caryophyllene. A Matlab mathematical procedure was developed to obtain the adjustable parameters of the mixing rules for both the binary and ternary mixture at the following temperatures: 313.2 K, 318.2 K and 328.2 K. Results show that the mixing rule that best fit the experimental data for the binary system CO2/clove oil is vdw2 with a %ΔP of 3.07%. For the ternary mixture, the mixing rule that best represent the experimental data is MKP with a %ΔP of 2.18%. The coupling among solubility calculation and mass transfer model described quantitatively very well the extraction experimental data. The coefficient of determination (R2) showed the minimum value of 0.9946 for conditions investigated.